Clearing the paradigmatic fog — how to move forward in business marketing research - Möller Kristian; Halinen AIno (Elsevier, 2022)
Although research in business-to-business (B2B) marketing has significantly increased, critical voices questioning the managerial relevance and theoretical innovativeness of the discipline abound. To find reasons for the alleged stagnation and forward the discipline, obtaining a better understanding of its current knowledge bases is essential. We aim to provide a meta-theoretical analysis of the B2B research domain by analyzing its major research communities and their paradigmatic ways of producing knowledge. The key premise is that the North American mainstream tradition (NAM) and the industrial marketing and purchasing (IMP) group-driven research approach form the dominant research cultures of B2B marketing. Paradigmatic profiling is used as a method of analysis for making the underlying assumptions and intellectual goals of the two communities transparent, enabling a rational assessment of their strengths and weaknesses. By contrasting the two paradigms, we highlight the fragmented knowledge base, identify neglected issues and unanswered questions, and suggest how to advance theory construction in the field. By analyzing the implicit assumptions and silent drivers of the NAM and IMP research communities, the study adds to our understanding of why we conduct this kind of research, how we can make better informed decisions concerning our studies, and how we might break free from the invisible paradigmatic cages to advance our discipline.